A fluorescence and UV/vis absorption dual-signaling probe with aggregation-induced emission characteristics for specific detection of cysteine. Issue 43 (5th July 2018) - Li, Ruru; Huang, Xiaoyu; Lu, Guolin; Feng, Chun
Abstract : A dual-signaling of fluorescence and UV/vis absorption modes for selective and quantitative detection of cysteine over homocysteine, N -acetyl-l -cysteine and glutathione is developed on the basis of aggregation-induced emission (AIE) effect. Abstract : Biological thiols with similar structures, such as glutathione (GSH), N -acetyl-l -cysteine (NAC), homocysteine (Hcy) and cysteine (Cys), play important roles in human physiology and are associated with different diseases. Thus, the discrimination of these thiols is a great necessity for various biochemical investigations and the diagnosis of related diseases. Herein, we present a new dual-signaling probe consisting of a typical aggregation induced emission fluorogen of a tetraphenylethylene group and 2, 4-dinitrobenzenesulfonyl moiety. The probe can be used to selectively and quantitatively detect Cys over a variety of bio-species, including GSH, NAC and Hcy, from both UV/vis absorption and fluorescence channels. The mechanism study showed that the fluorescence and UV/vis absorption were turned on as the probe undergoes displacement of the 2, 4-dinitrobenzenesulfonyl group with Cys, where the UV/vis and fluorescence signals originate from the dinitrophenyl-containing compounds and aggregates of TPE-OH, respectively. In addition, the discrimination of Cys was achieved by more rapid intramolecular displacement of sulfur with the amino group of Cys than NAC, Hcy and GSH. Moreover, the probe shows ignorable cytotoxicity against HepG2 cells, which demonstrates the great potential of the probe in selectively detecting Cys in vivo .